Navigating Global Cosmetics Compliance: A Comparative Analysis of India's Cosmetics Rules 2020 with International Standards - Akram, Afifa; Singh, Indu; Chauhan, Shikha Baghel (Current Drug Research Reviews, 2025)
The Indian cosmetics industry has undergone a significant transformation with the implementation of the Cosmetics Rules 2020, which seek to align the country's regulatory framework with international standards, address local challenges, and ensure consumer safety. These rules cover registration and licensing, labeling and packaging, and stringent safety standards, ensuring the production of high-quality, safe products. This review provides a detailed comparative analysis of India's new regulations with those in major markets, including the European Union (EU), the United States (US), and Japan, as well as emerging markets such as China, Brazil, and Southeast Asia. The analysis highlights key similarities and differences, identifies areas for further reform, and offers insights into global regulatory dynamics. The review examines critical aspects such as registration and licensing requirements, which are essential for market entry. It also scrutinizes labeling and packaging regulations, which promote consumer transparency. Safety standards are a focal point, given their importance in protecting consumers. The impact of these regulations on India's cosmetics industry is explored, emphasizing the growing importance of sustainable practices, digital labeling, and traceability systems. These technologies enhance consumer access to product information and ensure product authenticity and safety throughout the supply chain. Furthermore, this review provides a future outlook, suggesting areas for regulatory improvement to support continued industry growth and consumer protection by examining current regulations and emerging trends.
Keywords: emerging markets